Kredibilitas Juru Dakwah sebagai Komunikator - Rahmah, Mariyatul Norhidayati (Alhadharah: Jurnal Ilmu Dakwah, 2013)
Muslim preacher must have a high credibility be able to invite mankind to do good and avoid His prohibitions. High and low credibility of a preacher who portray himself as a communicator depends on public perception and social conditions in which he/she preaches. In this regard, there are many components of the assessment as an indicator whther the preacher considered as having high credibility in the eyes of society . One of the preachers may be deemed to have high credibility, when the assessment is viewed from the perspective of the people who focus more on formal education for example , or for some other people, which is important these preachers based schools and so on , of course the assessment is also supported by another component, so it can be said that preachersâ credibility is relative, but it should have to be comprehensive. Thus the level of credibility of the preacher can not be seen from one side only but must be viewed from a variety of other related components